DEUTRAGONIST’S EGOISM IN JOJO MOYES’ NOVEL ME BEFORE YOU - Adelia Febriana Lubis; Muhammad Ali Pawiro (JOURNAL OF LANGUAGE, 2022)
This study is to explore the deutragonist’s egoism in Jojo Moyes Novel Me Before You. The study focuses on the accidental meeting between Will and Louisa which makes them fall in love but they do not end up together. Their love does not make Will egoistic to go away and not to change his decision to end his life. It takes an analysis on psychological egoism and ethical egoism. Additionally, the analysis is concerned with the two characteristics of deutragonist’s egoism before and after the accident. This study used a qualitative method to find evidence from the data identified from the novel. The analysis is done by classifying the data related to the research problem. The results of this study indicate that Will’s egoism cannot be imitated, and it is not accepted in an environment such as committing suicide. The obstacles and struggles of the second character are found to fulfill his needs which are also related to the love story in the novel.